2019
DOI: 10.3390/admsci9030062
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Universities in Sustainability-Oriented Competencies Development: Insights from an Empirical Study on Polish Universities

Abstract: The growing importance of sustainable development constitutes a challenging trend for education. Universities create study programs and organize extracurricular activities in order to prepare future generations of professionals as well as political and social leaders for responsible actions toward sustainable development. The main objective of this article is to investigate how universities in Poland develop educational programs and extracurricular activities to enable students to shape sustainability competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Education for sustainable development is a concept that has been debated upon by a lot of researchers [14,16,17,22,28,34] based on the fact that: "An empowering education is one that builds the human resources we need to be productive, to continue to learn, to solve problems, to be creative, and to live together and with nature in peace and harmony. When nations ensure that such an education is accessible to all throughout their lives, a quiet revolution is set in motion: education becomes the engine of sustainable development (economic, social, moral, intellectual, and cultural) and the key to a better world" [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Education for sustainable development is a concept that has been debated upon by a lot of researchers [14,16,17,22,28,34] based on the fact that: "An empowering education is one that builds the human resources we need to be productive, to continue to learn, to solve problems, to be creative, and to live together and with nature in peace and harmony. When nations ensure that such an education is accessible to all throughout their lives, a quiet revolution is set in motion: education becomes the engine of sustainable development (economic, social, moral, intellectual, and cultural) and the key to a better world" [65].…”
Section: Discussionmentioning
confidence: 99%
“…Acting sustainably means that individuals first need to acquire sustainability-oriented competencies that can be developed through education and by introducing innovative forms of teaching and learning and reinforced through media communication and community actions. Sady et al (2019) identified the core competencies of sustainability, namely: Responsibility (ethics), critical thinking, future orientation, communication and collaboration, systemic thinking and learning [16].…”
Section: Education For Sustainable Development (Esd) and Sustainabilimentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship today is conceptualised as a universal set of skills and attitudes that can be applied in every context, and that is essential at all stages of a professional career [1,2]. Employee-level entrepreneurial competence is often indicated by research and practice as the prime type of competence, necessary in today's business reality to handle proactively contemporary workplace challenges [3][4][5][6]. This is why employees often seek to develop their entrepreneurial skills throughout their career by pursuing continuous lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…University education is the focus of attention of all countries, due to the great role that university education plays in preparing and making future generations, the main drive for economic and social sectors (Sady et al, 2019). In light of the increased competition in the educational sector in the Arab countries and the shortage of job opportunities faced by university graduates, these universities should, Arab universities should re-double their efforts to build an educated person capable of actively taking part in achieving the development programs that help such countries compete at the local, regional, and global levels (Issa & Siddiek, 2012).…”
Section: Introductionmentioning
confidence: 99%